1991
DOI: 10.1366/0003702914337489
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon Solute Probes. Part VIII: Evaluation of Additional Naphthacene and Perylene Derivatives as Possible Solvent Polarity Probe Molecules

Abstract: Fluorescence emission spectra are reported for phenanthro[5,4,3,2efghi]perylene, dibenzo[cd,k]naphtho[8,1,2fghi]perylene, benzo[b]peryiene, dibenzo[e,ghi]perylene, and benzo[a]naphtho[8,1,2cde]-naphthacene dissolved in various organic solvents. Results of these measurements are used to screen PAHs for potential solvent polarity behavior. Of the five PAHs studied, only phenanthro[5,4,3,2efghi]perylene exhibited probe behavior, as evidenced by selective emission intensity enhancement of band I with increasing so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…The fluorescence decay profiles recorded for TEP and TEP-TMS followed a single exponential kinetics in all the solvents studied. A relatively short excited state lifetime (2-4 ns) was observed when compared to pyrene, which normally shows a quite high lifetime reaching 390 ns in non-polar solvents [17]. Molecules with a strongly allowed S 0 -S 1 transition usually exhibit short lifetimes.…”
Section: Fluorescence Lifetime Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluorescence decay profiles recorded for TEP and TEP-TMS followed a single exponential kinetics in all the solvents studied. A relatively short excited state lifetime (2-4 ns) was observed when compared to pyrene, which normally shows a quite high lifetime reaching 390 ns in non-polar solvents [17]. Molecules with a strongly allowed S 0 -S 1 transition usually exhibit short lifetimes.…”
Section: Fluorescence Lifetime Studiesmentioning
confidence: 99%
“…A systematic experimental investigation on a series of polycyclic aromatic hydrocarbons (PAHs) [8,9,10,11,12,13,14,15,16,17,18] for a variation in selective vibronic bands with respect to solvent polarity show that the PAHs broadly fall in to three categories. The first category of PAHs include pyrene, benzo[ghi]perylene, etc which exhibit a selective emission intensity enhancement of vibronic band I relative to band III (I/III) in polar solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent misidentification, the data file should include both polar and nonpolar solvents, since electronic interactions between a solvent dipole and an excited PAH/PANH solute can lead to spectral distortions, wavelength shifts and/or intensity ratio variations, as was the case with many of the polycyclic aromatic compounds examined previously. [10][11][12][13][14][15][16][17][18][19][20][21] Solvent-induced fluorescence spectral changes can be rationalized qualitatively in a relatively straightforward Received 15 July 1991; revision received 9 August 1991. * Author to whom correspondence should be sent.…”
Section: Introductionmentioning
confidence: 99%
“…For many larger hydrocarbons it was observed that the intensities of vibronic components in the absorption spectra vary in different solvents [6][7][8][9][10], which indicates the presence of several forms. For tetrabenzo[α, cd, f, lm]perylene, a discrepancy between absorption and fluorescence excitation spectra was interpreted (295) as evidence of more than one conformer present at room temperature [11].…”
mentioning
confidence: 99%